Quercetin Directly Interacts with Vitamin D Receptor (VDR): Structural Implication of VDR Activation by Quercetin - Lee, Ki-Young (Biomol Ther (Seoul), 2016)
The vitamin D receptor (VDR) is a member of the nuclear receptor (NR) superfamily. The VDR binds to active vitamin D(3) metabolites, which stimulates downstream transduction signaling involved in various physiological activities such as calcium homeostasis, bone mineralization, and cell differentiation. Quercetin is a widely distributed flavonoid in nature that is known to enhance transactivation of VDR target genes. However, the detailed molecular mechanism underlying VDR activation by quercetin is not well understood. We first demonstrated the interaction between quercetin and the VDR at the molecular level by using fluorescence quenching and saturation transfer difference (STD) NMR experiments. The dissociation constant (K(d)) of quercetin and the VDR was 21.15 ± 4.31 μM, and the mapping of quercetin subsites for VDR binding was performed using STD-NMR. The binding mode of quercetin was investigated by a docking study combined with molecular dynamics (MD) simulation. Quercetin might serve as a scaffold for the development of VDR modulators with selective biological activities.